2019
DOI: 10.14421/grieb.2019.071-02
|View full text |Cite
|
Sign up to set email alerts
|

What Determines Sukuk Market Development? New Theoretical Insights

Abstract: In recent past, the Asian economies faced various financial crises, 1997 & 2008, because of underdeveloped or small capital markets. Most of the countries continued to heavily depend on the mere banking system for sovereign and corporate financing needs which made the region repeatedly vulnerable to the crises state. Therefore, the last decade has witnessed the remarkable growth in the alternative arrangement in the form sukuk and bond markets. The academic literature on the topic mainly focuses on bond ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…However, the relevant empirical literature on the topic is very limited. Some of the notable empirical works on sukuk have been done by Adam and Thomas (2004), Wilson (2008), Jaffer (2011), Godlewski et al (2013), Van Wijnbergen and Zaheer (2013), Azmat et al (2014), Smaoui et al (2017) and Aman et al (2019aAman et al ( , 2019b. The focus of these prior studies is on firm specific attributes of sukuk, like the capital structure of the firm, pricing of the sukuk and suitable underlying assets for sukuk.…”
Section: Theoretical Relationships and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the relevant empirical literature on the topic is very limited. Some of the notable empirical works on sukuk have been done by Adam and Thomas (2004), Wilson (2008), Jaffer (2011), Godlewski et al (2013), Van Wijnbergen and Zaheer (2013), Azmat et al (2014), Smaoui et al (2017) and Aman et al (2019aAman et al ( , 2019b. The focus of these prior studies is on firm specific attributes of sukuk, like the capital structure of the firm, pricing of the sukuk and suitable underlying assets for sukuk.…”
Section: Theoretical Relationships and Literature Reviewmentioning
confidence: 99%
“…In addition, Asian economies are in the phase of developing infrastructural connections within as well as across the economies; therefore, they need huge long term finances. These financial needs can be met through mobilizing local as well as regional capital resources with the help of having established sukuk and bonds markets (Aman et al, 2019a(Aman et al, , 2019bMusa et al, 2020). Well-developed sukuk and bond markets will simultaneously make Asia more resilient to the economic crises, attract the foreign capital inflows and turn the regional savings of Asia into fruitful investments (Bhattacharyay, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The same results were also found in a study conducted by Al-Raeai et al (2018) who studied in the country -the gulf states that sukuk can increase or reduce economic growth through exchange rate and inflation. The study conducted by Alkhawaja (2019), Muharam et al (2019), andAman et al (2019) found that sukuk can influence economic growth through investment and trade openness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using content analysis approach, Aman et al. (2019) theoretically investigated the determining factors likely to contribute to SMD.…”
Section: Literature Reviewmentioning
confidence: 99%